Seasonal variation in haematological parameters in crossbred horses used for urban traction from Lages, SC, Brazil - Souza, Anderson Fernando de; Signor, Jonas; Schade, Jackson; Saito, Mere Erika; Muller, Thiago Rinaldi; Fonteque, Joandes Henrique (Archives of Veterinary Science, 2018)
The aim of this study was to evaluate the influence of seasons on the hematological profile in horses used for urban traction in the city of Lages, Brazil. Blood samples were collected of the twenty crossbreed horses used for urban traction in the city of Lages, Brazil, carried out in four different periods according to the seasons, for carrying out the hematological profile, plasma total protein (PTP) and plasma fibrinogen. PTP was determined by refractometry method and the determination of plasma fibrinogen by heat precipitation method. Climate variations, such as maximum and minimum temperature, relative humidity and rainfall index for each period were obtained through access to the Center of Environmental Resources Information and Hydrometeorology of Santa Catarina. All values found were within the reference values commonly used for equine specie. There was no significant difference throughout the seasons on the values of erythrogram, leukogram, neutrophil-lymphocyte ratio and PTP. The MCH and plasma fibrinogen were higher in summer and eosinophils had significantly higher values in winter followed by summer. The region of Lages presents marked seasonal fluctuations, and these have little influence on hematological characteristics in horses used for urban traction.